2015
DOI: 10.1007/s10973-015-5031-0
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of heat transfer characteristics of CuO–water nanofluid by Euler–Lagrange approach

Abstract: The two-phase Euler-Lagrange method is used here to study heat transfer characteristics of the CuO-water nanofluid in a straight tube under laminar flow regime. The comparison between two-phase and single-phase approaches shows that the Euler-Lagrange method presents more accurate results. The convective heat transfer coefficient increases with increment of particle concentration. Moreover, the amount of heat transfer enhancement increases along the tube length. The thermophoretic and Brownian forces affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…5a and all other plots the p-Q relationship is clearly an inverse linear relationship i.e. pressure difference decreases with increasing volumetric flow rate which is also characteristic of peristaltic propulsion systems [52]. (Fig.…”
Section: Numerical Results and Interpretationmentioning
confidence: 70%
See 1 more Smart Citation
“…5a and all other plots the p-Q relationship is clearly an inverse linear relationship i.e. pressure difference decreases with increasing volumetric flow rate which is also characteristic of peristaltic propulsion systems [52]. (Fig.…”
Section: Numerical Results and Interpretationmentioning
confidence: 70%
“…Further analyses have been communicated by Medhavi and Singh [48], Kamel et al . [49], Bahiraei [50,51,52], Bahiraei et al [53,54,55] the latter also addressing multi-phase flows.…”
Section: U Sir Is a DI Git Al C Oll E C Tio N Of T H E R E S E A R C mentioning
confidence: 99%
“…Several comparative reports also emphasised the accuracy of this approach [24][25][26][27][28]. However, a group of researchers condemned homogenous approximation of highly concentrated nanofluids due to the significant influence of interphase interactive forces that are neglected in this approach [2,[29][30][31][32][33][34][35][36][37]. Analysing forced convection of Al2O3/H2O, TiO2/H2O and Cu/H2O nanofluids, Nishat et al [38] demonstrated that the homogeneous model accurately predicts the highly concentrated nanofluids (0.5% ≤ φ ≤ 2%) compared with the Lagrangian-Eulerian model.…”
Section: Introductionmentioning
confidence: 99%
“…In a comparative evaluation of single-phase and Eulerian-Eulerian models, Akbari et al [25,31] stated that Eulerian, mixture and VOF models overpredict the convective heat transfer coefficient of highly concentrated Al2O3/H2O (0.6% ≤ φ ≤ 1.6%) nanofluid. For the Lagrangian-Eulerian approach, several reports endorsed its superiority [32][33][34]36,42], but a few conflicting reports claimed otherwise [26]. The possible justifications of these contradictions are the insufficient nanofluid-related numerical investigations, lack of understanding of physical phenomena responsible for the enhanced thermal activity of nanofluids and inaccurate modelling.…”
Section: Introductionmentioning
confidence: 99%
“…The present work investigates the nanorefrigerant flow though a circular tube in turbulent regime wherein R718 (water) is the base refrigerant which is utilised as a secondary refrigerant in refrigeration systems. The nanofluid turbulent flow through a circular tube has been experimentally and numerically studied by several researchers [30][31][32][33][34]. Azmi et al [35] conducted experiments at a bulk fluid temperature of 30 °C to investigate the heat transfer performance of TiO 2 and SiO 2 nanofluids under turbulent flow scenario and noticed an enhancement in the heat transfer coefficient up to 26% at a particle volume fraction of 1%.…”
Section: Introductionmentioning
confidence: 99%